2016
DOI: 10.3390/w8070303
|View full text |Cite
|
Sign up to set email alerts
|

Navigating towards Decoupled Aquaponic Systems: A System Dynamics Design Approach

Abstract: Abstract:The classical working principle of aquaponics is to provide nutrient-rich aquacultural water to a hydroponic plant culture unit, which in turn depurates the water that is returned to the aquaculture tanks. A known drawback is that a compromise away from optimal growing conditions for plants and fish must be achieved to produce both crops and fish in the same environmental conditions. The objective of this study was to develop a theoretical concept of a decoupled aquaponic system (DAPS), and predict wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 64 publications
(48 reference statements)
1
115
0
2
Order By: Relevance
“…The few facilities with high fish production seemed to be tending towards decoupled systems where waste-water can be alternatively given to plants or passed through a biofilter [9]. Most of the current aquaponic units were new and funded by government subsidies.…”
Section: Discussionmentioning
confidence: 99%
“…The few facilities with high fish production seemed to be tending towards decoupled systems where waste-water can be alternatively given to plants or passed through a biofilter [9]. Most of the current aquaponic units were new and funded by government subsidies.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Neto and Ostrensky [76] proposed that 17% of the feed input for nitrogen and 37% for phosphorus is lost as nutrients from the faeces in Nile tilapia reared in cages. Although the data of Neto and Ostrensky [76] were based on cage breeding systems, recently Goddek et al [26] observed similar values in RAS. Certainly, the species affects the entity of these losses, which are affected also by the physiological stage within the species.…”
Section: Wastes and Faecesmentioning
confidence: 98%
“…Most plants require a pH value between 5.5 and 6.5 to enhance the uptake of nutrients. However, the optimal pH of three major bacteria has been stated as (1) Nitrobacter: 7.5; (2) Nitrosomonas: 7.0-7.5; and (3) Nitrospira: 8.0-8.3 [26]. However, in terms of the tolerance of fish to pH changes based on fish species and size, the recommended pH for aquaculture is 6.5-8.5 [27].…”
Section: Water Qualitymentioning
confidence: 99%
“…The results achieved from the operation of the pilot units [3] and other EU-funded projects [6,7] show that the circular models offer resource efficient food production by closing the water cycle for reuse of nutrients-producing fish and plants in an integrated system. However, due to the differences in optimum environmental parameters for the fish and plants, there is a need to decouple the two production systems in competitive commercial-scale systems (Figure 1).…”
Section: Pilot Casementioning
confidence: 99%